Funduscopy in Adult Zebrafish and Its Application to Isolate Mutant Strains with Ocular Defects - Tschopp, Markus (Public Library of Science, 2010)
Funduscopy is one of the most commonly used diagnostic tools in the ophthalmic practice, allowing for a ready assessment of pathological changes in the retinal vasculature and the outer retina. This non-invasive technique has so far been rarely used in animal model for ophthalmic diseases, albeit its potential as a screening assay in genetic screens. The zebrafish (Danio rerio) is well suited for such genetic screens for ocular alterations. Therefore we developed funduscopy in adult zebrafish and employed it as a screening tool to find alterations in the anterior segment and the fundus of the eye of genetically modified adult animals. A stereomicroscope with coaxial reflected light illumination was used to obtain fundus color images of the zebrafish. In order to find lens and retinal alterations, a pilot screen of 299 families of the F3 generation of ENU-treated adult zebrafish was carried out. Images of the fundus of the eye and the anterior segment can be rapidly obtained and be used to identify alterations in genetically modified animals. A number of putative mutants with cataracts, defects in the cornea, eye pigmentation, ocular vessels and retina were identified. This easily implemented method can also be used to obtain fundus images from rodent retinas. In summary, we present funduscopy as a valuable tool to analyse ocular abnormalities in adult zebrafish and other small animal models. A proof of principle screen identified a number of putative mutants, making funduscopy based screens in zebrafish feasible.